2015
DOI: 10.1152/ajpheart.00536.2014
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependency of aortic pulse wave velocity in vivo is not affected by vasoactive substances that alter aortic wall tension ex vivo

Abstract: Aortic stiffness, a predictive parameter in cardiovascular medicine, is blood pressure dependent and experimentally requires isobaric measurement for meaningful comparison. Vasoactive drug administration to change peripheral resistance and blood pressure allows such isobaric comparison but may alter large conduit artery wall tension, directly changing aortic stiffness. This study quantifies effects of sodium nitroprusside (SNP, vasodilator) and phenylephrine (PE, vasoconstrictor) on aortic stiffness measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…; Butlin et al . ) and here we confirm that it provides a sufficiently sensitive and practical method to estimate transluminal pressure to evaluate the effects of distension pressure and VSMC tone. Secondly, perfusion‐based set‐ups expose the endothelial cells to shear stress, a well‐known stimulator of endothelial NO production.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…; Butlin et al . ) and here we confirm that it provides a sufficiently sensitive and practical method to estimate transluminal pressure to evaluate the effects of distension pressure and VSMC tone. Secondly, perfusion‐based set‐ups expose the endothelial cells to shear stress, a well‐known stimulator of endothelial NO production.…”
Section: Discussionsupporting
confidence: 82%
“…A study that compared the effects of vasoactive substances on the aorta found large differences in vivo versus ex vivo (Butlin et al . ) and visco‐elastic properties of the aorta change significantly after isolation of the aorta from the animal (Boutouyrie et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo vascular stiffness was examined by obtaining invasive PWV measurements at mean arterial pressures varying from 55 to 130 mm Hg as previously described . We used a high‐fidelity dual‐pressure catheter sensor to measure aortic PWV.…”
Section: Methodsmentioning
confidence: 99%
“…In mouse aortic segments, implemented preloads are highly variable among different studies and range from about 1.2–8.0 mN/mm (Fransen et al, 2008, 2015; Van Hove et al, 2009; Ponnoth et al, 2012; van Langen et al, 2012; Lloyd et al, 2013; Taguchi et al, 2014; Gross et al, 2015; Leloup et al, 2015a; Zhou et al, 2015). According to Laplace's law, and assuming a thin, isotropic and homologous wall for large vessels such as the aorta, the transmural pressure (P, in mm Hg) is directly proportional to the preload (PL, in mN) and inversely proportional to its length (l, in mm) and radius (r, in mm): P = PL/(l × 2r) × 7.5) (Syyong et al, 2009; Van Herck et al, 2009; Butlin et al, 2015). Preloads between 1.2 and 8.0 mN/mm roughly correlate with transmural pressures from 10 to 65 mmHg and are sub-physiological.…”
Section: Introductionmentioning
confidence: 99%